Effect of Valproate and Antidepressant Drugs on Clozapine Metabolism in Patients With Psychotic Mood Disorders. Issue 4 (August 2018) - Marazziti, Donatella; Palego, Lionella; Betti, Laura; Giannaccini, Gino; Massimetti, Enrico; Baroni, Stefano; Ciapparelli, Antonio; Lucacchini, Antonio; Mucci, Federico; Dell'Osso, Liliana
Abstract : Background: The aim of the present study was to appraise retrospectively the influence of valproate (VPA) and antidepressants (ADs) on the steady-state plasma concentrations of clozapine (CLZ), the prototype of various second-generation antipsychotics, norclozapine (NCLZ, its main metabolite), and their ratio (NCLZ:CLZ). Methods: Sixty-seven psychotic patients with a prevalent diagnosis of bipolar disorder were studied. We then analyzed data altogether and subdivided them into 4 groups, according to pharmacological treatments: #1 CLZ (n = 21), #2 CLZ plus ADs (n = 13), #3 CLZ plus VPA (n = 16), and #4 CLZ plus ADs plus VPA (n = 17). Results: First, significant positive between CLZ and NCLZ plasma levels (in nanograms/milliliter) and the drug daily dosages (in milligrams/kilogram of body weight) (n = 67) were observed (Spearman: rCLZ = 0.49; rNCLZ = 0.61; P < 0.001). We then normalized by given doses CLZ and NCLZ plasma levels, natural log transformed them, and performed analysis of variance factor analyses followed by pairwise comparisons, performed on the 4 groups and the 3 CLZ parameters. We identified significant drug effects on (1) CLZ plasma levels, significantly higher in group #2 versus group #1, and (2) NCLZ:CLZ ratio, lower in group #2 versus groups #1 and #3. Significant drug × gender interactions were observed in group #3, showing higher NCLZ levels and NCLZ:CLZ ratios in men compared with women. Conclusions: Despite its inherent limitations, this observational study confirms the significant increase in plasma CLZ concentrations and reduction in NCLZ:CLZ ratio when this drug was coadministered with ADs (group #2), an effect apparently counteracted by VPA (group #4). The drug × gender interactions in patients taking both CLZ and VPA (group #3) warrant further prospective study.